Education on community empowerment in prevention of Covid-19 to the community Laut Dendang village, Percut Sei Tuan district Deli Serdang regency - Mardiningsih; Suwilo, Saib; Mawengkang, Herman; Sutarman; Marpongahtun (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Community Service Activities carried out by the Service Team are intended to achieve the output target of reducing the spread of covid-19 in the people of Laut Dendang Village. The community service team conducts outreach regarding improving the quality of health and education in this village, in this case the Village Head, Hamlet Head, and PKK women become participants in this outreach, so that further all participants can socialize the issue of the importance of preventing Covid-19 and how to do it. prevention. It is hoped that the improvement of the quality of health in this village can be a lesson for the village community to understand and implement all knowledge or rules in reducing or stopping the spread of this deadly virus. This service is aimed at Community Service for the 2020 USU Lecturer Service Scheme is to solve problems together with the community through observation, problem identification, problem formulation, preparation of alternative solutions and evaluation of their implementation.